Four Decades of Research into Children's Reading Comprehension: A Personal Review. Issue 5 (2nd July 2020) - Oakhill, Jane
ABSTRACT: A substantial amount of research has focused on children's reading development and reading problems, but in comparison there has been relatively little research into children's reading comprehension. This article provides an overview of the research that has investigated the skills and cognitive processes that support children's understanding of text and reflects on the implications of the findings presented in helping children to develop and improve their comprehension skills. The article concludes by considering which avenues of investigation still need further exploration.